Genome of Argania spinosa L.: insights into oil production and the tocopherol biosynthesis pathway - Oliver Rupp; Clemens Roessner; Naemi Lederer-Ponzer; Tassilo Erik Wollenweber; Annette Becker; Mouna Lamaoui (Genetic Resources and Crop Evolution, 2024)
Argan ( Argania spinosa L.) is a highly valued tree for its multiple uses as food and feed and for being linked to a broad range of benefits of pharmaceutical and cosmetic relevance. This multipurpose resource is becoming increasingly overused, which may disrupt the whole ecosystem’s sustainability. Due to the high socio-economic status of this tree, research interventions are needed to reverse the forest regressive trend, restore the disturbed ecosystem, and conserve genetic diversity. However, research on argan is restricted by the lack of accessible information on the genetic and genomic bases of the species, specifically a functional annotated genome. Herein, we report the reference transcriptome aided annotation of the argan tree genome using de novo gene prediction programs aided by homology information from different plants. The results of the genome annotation using AUGUSTUS were subsequently improved by performing RNA sequencing. A total of 62,590 gene loci could be identified with 82,286 isoforms and a BUSCO completeness of 91.7%. To gain insight into the agronomically important compounds in argan oil, a comparative genome analysis and ortholog identification was performed, followed by phylogenetic tree construction of the main biosynthesis genes. Among those are fatty acids and tocopherols, the latter being the main factor behind the increasing demands for argan oil. Our analysis is the initial step to provide breeders, geneticists, and the industries with adequate genomic information, facilitate improvement of economically important traits and to selectively adapt the tree to the increasing impact of climate change.